Improvement of Methods of Treating Atypical Pneumonia of Mycoplasmal Etiology in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pneumonia, or inflammation of the lungs, is dangerous not only for children but also for adults. This is primarily due to the risk of serious complications, pulmonary edema, including lung abscess, pleurisy, pleural empyema, obstruction, endocarditis, acute respiratory failure, pericarditis, sepsis. One of the most common diseases in children is pneumonia, which occupies a worthy place in terms of morbidity and mortality. We treated 48 patients aged 3 to 14 years, who were divided into 2 groups. 24 patients were prescribed complex therapy, which included antibacterial drugs and antiviral drugs in age-appropriate doses for 10 days. The clinical manifestations of group I improved almost 2 times faster than in patients in group II. For accurate verification of the pathogen, laboratory methods of diagnosing atypical pneumonia are used: bacteriological culture of sputum, nasopharyngeal swabs on nutrient media; ELISA, RSC, radioimmunoassay, RIF, PCR. Timely and adequate etiotropic therapy promotes rapid regression of clinical manifestations of atypical mycoplasma pneumonia. Meanwhile, radiographic changes can persist for a long time, up to 4-6 weeks. In the therapy of atypical pneumonia caused by mycoplasma, macrolides (azithromycin, erythromycin), lincosamines (clindamycin) are used in the main course of at least 7 days and an additional one - 2 days after the symptoms subside. At the same time, symptomatic (antipyretic, mucolytic, bronchodilator) therapy is carried out, glucocorticosteroids are prescribed for bronchiolitis. Complex treatment of antibiotics and antiviral drugs for atypical pneumonia showed that they are most effective in reducing the severity of the disease. Thus, the combined use of antibacterial and antiviral drugs in the treatment of atypical pneumonia in children is effective. Ease of use, the availability of a drinkable form of the drug, high efficacy and the absence of significant side effects allow us to recommend this treatment for widespread use in pediatrics. Based on the above, the combined use of antibacterial and antiviral drugs for the treatment of patients with inflammatory diseases of the upper and lower respiratory tract may be recommended.